The riddle of Zorfendorf Castle - Abbott, Tony.; Merrell, David (New York : Scholastic, 2005)
Eric and his friends must stop Emperor Ko from finding a secret hidden underneath Zorfendorf Castle.
"A Little Apple paperback."
4.4
3-6
3-6
630
Keywords: Droon (Imaginary place) -- Fiction; Magic -- Fiction; Fantasy; Castles -- Fiction; Droon (Imaginary place) -- Fiction; Magic -- Fiction; Fantasy fiction; Castles -- Fiction